2015
DOI: 10.1186/s13075-015-0741-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of systemic lupus erythematosus patients with the BAFF antagonist “peptibody” blisibimod (AMG 623/A-623): results from randomized, double-blind phase 1a and phase 1b trials

Abstract: IntroductionBlisibimod is a potent B cell-activating factor (BAFF) antagonist that binds to both cell membrane-expressed and soluble BAFF. The goal of these first-in-human studies was to characterize the safety, tolerability, and pharmacokinetic and pharmacodynamic profiles of blisibimod in subjects with systemic lupus erythematosus (SLE).MethodsSLE subjects with mild disease that was stable/inactive at baseline received either a single dose of blisibimod (0.1, 0.3, 1, or 3 mg/kg subcutaneous [SC] or 1, 3, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 45 publications
(44 reference statements)
3
36
0
1
Order By: Relevance
“…Blisibimod (A-623, AMG 623) is a potent and selective BAFF inhibitor composed of a tetrameric BAFF binding domain fused to a human IgG1 Fc region 9. Although the phase II Placebo-controlled Evaluation of A‑623 Response in Lupus (PEARL-SC) trial with blisibimod in SLE failed to meet the primary efficacy end point, SLE Responder Index-5 (SRI-5), it corroborated the observations from larger Phase III trials in that better treatment effect was observed in subjects with higher disease activity, taking corticosteroids, who had abnormalities in anti-dsDNA and/or complement 10.…”
Section: Introductionmentioning
confidence: 99%
“…Blisibimod (A-623, AMG 623) is a potent and selective BAFF inhibitor composed of a tetrameric BAFF binding domain fused to a human IgG1 Fc region 9. Although the phase II Placebo-controlled Evaluation of A‑623 Response in Lupus (PEARL-SC) trial with blisibimod in SLE failed to meet the primary efficacy end point, SLE Responder Index-5 (SRI-5), it corroborated the observations from larger Phase III trials in that better treatment effect was observed in subjects with higher disease activity, taking corticosteroids, who had abnormalities in anti-dsDNA and/or complement 10.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is blisibimod, a Bpeptibody^made of four BAFF binding domains linked to the Fc domain of human IgG1 and which, unlike belimumab, binds to both membrane-bound and soluble BAFF. In phase I RCTs, this agent was well tolerated and led to decreases in total B cell counts, reductions in the naïve B cells, and transient increases in the memory B cells [74].…”
Section: Blisibimodmentioning
confidence: 99%
“…Recent treatments that have been reported but are in need of further study include lenalidomide, a thalidomide derivative [7779]; octreotide, a peptide analog of somatostatin [112]; mizoribine, an immunosuppressive [113]; and blisibimod, a biologic BAFF inhibitor [114], among others. Likewise, treatments such as intravenous immunoglobulin therapy [115], mesenchymal stem cell transplantation [116], and regulatory T cell therapy [117] that have shown success in other diseases are now being applied to CLE in exploratory studies.…”
Section: Five-year Viewmentioning
confidence: 99%